Nature of the progressed Grade 12 learners’ self-esteem at schools in the Motheo education district - Khobe Mamello (International Journal of Studies in Psychology)
The practice of progression or social promotion at schools is a concern in the South African education system and worldwide. The practice has raised many theoretical and practical concerns regarding its impact on the progressed learners’ self-esteem. This study sought to determine the progress of grade 12 learners’ self-esteem at high schools. It was embedded within a postpositivism paradigm as reinforced by a quantitative research methodology, and a face-to-face survey research design was adopted. Fifty (N=50) respondents (females = 29, males = 21) were conveniently and purposefully selected from five high schools in the Motheo Education District. Data were collected through questionnaires. The findings demonstrated that progression negatively impacted the progressed grade 12 learners’ self-esteem and needed to be mitigated at schools. This study recommended that the South African Department of Basic Education should capacitate schools to become centres of care and support for teaching and learning.